Targeted camptothecin delivery via silicon nanoparticles reduces breast cancer metastasis. (May 2020) - Landgraf, Marietta; Lahr, Christoph A.; Kaur, Ishdeep; Shafiee, Abbas; Sanchez-Herrero, Alvaro; Janowicz, Phillip W.; Ravichandran, Akhilandeshwari; Howard, Christopher B.; Cifuentes-Rius, Anna; McGovern, Jacqui A.; Voelcker, Nicolas H.; Hutmacher, Dietmar W.
Abstract: In advanced breast cancer (BCa) patients, not the primary tumor, but the development of distant metastases, which occur mainly in the organ bone, and their adverse health effects are responsible for high mortality. Targeted delivery of already known drugs which displayed potency, but rather unfavorable pharmacokinetic properties, might be a promising approach to overcome the current limitations of metastatic BCa therapy. Camptothecin (CPT) is a highly cytotoxic chemotherapeutic compound, yet poorly water-soluble and non-specific. Here, CPT was loaded into porous silicon nanoparticles (pSiNP) displaying the epidermal growth factor receptor (EGFR)-targeting antibody (Ab) cetuximab to generate a soluble and targeted nanoscale delivery vehicle for cancer treatment. After confirming the cytotoxic effect of targeted CPT-loaded pSiNP in vitro on MDA-MB-231BO cells, nanoparticles were studied in a humanized BCa bone metastasis mouse model. Humanized tissue-engineered bone constructs (hTEBCs) provided a humanized microenvironment for BCa bone metastases in female NOD-scid IL2Rg null (NSG) mice. Actively targeted CPT-loaded pSiNP led to a reduction of orthotopic primary tumor growth, increased survival rate and significant decrease in hTEBC and murine lung, liver and bone metastases. This study demonstrates that targeted delivery via pSiNP is an effective approach to employ CPT and other potent anti-cancer compounds with poor pharmacokinetic profiles in cancer therapy. Graphical abstract: Image 1 Highlights: Breast cancer (BCa) bone metastases are incurable with current treatment options. The humanized tissue-engineered bone construct (hTEBC) can be used to test treatments against BCa bone metastases in vivo. CPT-loaded porous silicon nanoparticles (pSiNP) showed significant therapeutic effect on BCa metastases in vivo. The modularity of the pSiNP nanomedicine allows for numerous future applications.